Pengaruh Ketepatwaktuan Publikasi Laporan Keuangan Terhadap Kandungan Kualitas Informasi Laba Akuntansi di Pasar Modal Indonesia - made gede wirakusuma (The Indonesian Journal of Accounting Research, 2013)
The main objective of this research is to investigate the effect of timeliness on the information quality of accounting earnings. In addition, the study also examines the effect of  timeliness differences on the information content of accounting earnings. I use two measures of timeliness: absolute timeliness and relative timeliness. Absolute timeliness is defined as (1) the length of reporting delay since the reporting date of financial statement and (2) the length of reporting delay since the date of the report signed by the independent auditor but it is still under the time allowed by the authority (BAPEPAM). On the other hands, relative timeliness is defined as (1) the difference between the length of reporting delay of current and previous report, or (2) weighted scores of the difference between the length of reporting delay of current and previous report.  The length of reporting delay is measured by the number of day toward the deadline date set by market authority (BAPEPAM).  Thus, the higher the number of day toward the deadline means that firms publish their report more timely. Using 122 company’s audited annual financial statement from the period of 2003 to 2005, the study shows that timeliness, particularly absolut timeliness, is positively associated with the information quality of accounting earnings suggesting that delaying publication of financial report will decrease the quality of information content. In addition, the study also finds that consistent with previous studies, other factors such as risk, market to book value, capital structure, and size together determine the quality of information of accounting earning. The result of the study should be of interest to the market authority, BAPEPAM in particular, to put efforts to increase the value relevance of accounting information by increasing the timeliness.